2023
DOI: 10.3389/fneur.2023.1123165
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal posterior semicircular canal function may predict poor prognosis in patients with severe and profound ISSNHL

Abstract: BackgroundSevere and profound idiopathic sudden sensorineural hearing loss (ISSNHL) generally leads to unfavorable prognosis, and has a considerable impact on patient quality of life. However, related prognostic factors remain controversial.ObjectiveTo elaborate the relationship between vestibular function impairment and the prognosis of patients with severe and profound ISSNHL, and investigated the relevant factors affecting prognosis.MethodsForty-nine patients with severe and profound ISSNHL were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Multiple studies have shown that patients with ISSSNHL also have clinical symptoms of dizziness, indicating that the vestibular organ may get involved. It was reported that nearly 40–55% of patients with ISSNHL suffered from vestibular dysfunction and were more commonly associated with severe hearing loss rather than mild and moderate hearing loss ( 8 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that patients with ISSSNHL also have clinical symptoms of dizziness, indicating that the vestibular organ may get involved. It was reported that nearly 40–55% of patients with ISSNHL suffered from vestibular dysfunction and were more commonly associated with severe hearing loss rather than mild and moderate hearing loss ( 8 13 ).…”
Section: Introductionmentioning
confidence: 99%